Efficient Catalysis of Hydrogen Evolution Reaction from WS2(1−x)P2x Nanoribbons. Issue 16 (6th February 2017) - Shifa, Tofik Ahmed; Wang, Fengmei; Liu, Kaili; Cheng, Zhongzhou; Xu, Kai; Wang, Zhenxing; Zhan, Xueying; Jiang, Chao; He, Jun
Abstract : The rational design of Earth abundant electrocatalysts for efficiently catalyzing hydrogen evolution reaction (HER) is believed to lead to the generation of carbon neutral energy carrier. Owing to their fascinating chemical and physical properties, transition metal dichalcogenides (TMDs) are widely studied for this purpose. Of particular note is that doping by foreign atom can bring the advent of electronic perturbation, which affects the intrinsic catalytic property. Hence, through doping, the catalytic activity of such materials could be boosted. A rational synthesis approach that enables phosphorous atom to be doped into WS2 without inducing phase impurity to form WS2(1− x ) P2 x nanoribbon (NRs) is herein reported. It is found that the WS2(1− x ) P2 x NRs exhibit considerably enhanced HER performance, requiring only −98 mV versus reversible hydrogen electrode to achieve a current density of −10 mA cm −2 . Such a high performance can be attributed to the ease of H‐atom adsorption and desorption due to intrinsically tuned WS2, and partial formation of NRs, a morphology wherein the exposure of active edges is more pronounced. This finding can provide a fertile ground for subsequent works aiming at tuning intrinsic catalytic activity of TMDs. Abstract : Doping by foreign atom into transition metal dichalcogenides affords the opportunity to improve the catalytic performance toward hydrogen evolution reaction. Following this concept, WS2(1− x ) P2 x is synthesized via simultaneously sulfurizing and phosphorizing WO3 nanowire on carbon fiber. The as‐obtained material is then directly used as electrocatalyst for hydrogen evolution reaction and superior catalytic performance is demonstrated therein.